Multidisciplinary approach to modern digital steganography - Pramanik, Sabyasachi, 1978-; Ghonge, Mangesh, 1984-; Ravi, Renjith, 1985-; Cengiz, Korhan (Advances in information security, privacy, and ethics (AISPE) book series., 2021)
"This book gives an insight to the different latest techniques and state-of-the-art methods, algorithms, architectures, models, methodologies, and case studies of steganography in the domain of Cloud, IoT and Android Platform"--